PENERAPAN METODE PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISIONS) UNTUK MENINGKATKAN PARTISIPASI DAN HASIL BELAJAR SISWA MATA PELAJARAN IPS PADA POKOK BAHASAN PERMINTAAN, PENAWARAN, DAN HARGA KELAS VIII-1 MTs NEGERI 4 KUANTAN SINGINGI - Lenny Lenny (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2023)
The purpose of this study was to increase student participation and learning outcomes in social studies subjects on the subject of demand, supply and price. The method used in this research is the STAD (Student Teams Achievement Divisions) Cooperative Learning method. This type of research is classroom action research, which uses an action research model from Suharsimi Arikunto that is from one cycle to the next cycle, where each cycle includes planning, implementation, observation and reflection. The steps for the next cycle include revised planning, implementation, observation, and reflection. From the results of student tests, it shows that in cycle I there were 6 complete students and 20 students who were not complete, the average score of all students was 45.77. Furthermore, in cycle II, students' understanding of the material has increased. This is evident from the test results showing that in cycle II, 17 students were complete and 9 students were not complete. The average score of all students was 78.15. Classroom action research on Demand, Supply, and Price material with the STAD method can be said to be successful because there is an increase from initial knowledge, cycle I, and cycle II.